The Influence of Product Quality and Price on Consumer Purchasing Decisions at Amalia Bakery - Putri Ramadhani; Annisa Sanny; Elfitra Desy Surya (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze product quality and price on consumer purchasing decisions at Amalia Bakery. The data used are primary data by collecting questionnaire data and analyzing it with the SPSS version 27 application. The research population was obtained by taking consumers who purchased the product and the sample was determined using the Slovin technique of 95 people. This study used multiple linear regression analysis. The results of the study partially show that product quality has a positive and significant effect on purchasing decisions, while price has a negative and significant effect on purchasing decisions. Furthermore, the results of the study simultaneously show that product quality and price have a positive and significant effect on purchasing decisions.